Supervisi Akademik untuk Mewujudkan Program Projek Penguatan Profil Pelajar Pancasila dan Profil Pelajar Rahmatan Lil Alamin (P5PPRA) di MA Al Fattahiyyah Tulungagung - Evy Ramadina (JoIEM (Journal of Islamic Education Management), 2025)
The purpose of this study is to describe the supervision process in the educational program for strengthening the Pancasila student profile and the Rahmatan Lil Alamin profile (P5PPRA). In the implementation of the independent curriculum in madrasahs, there are two student profiles related to the character of students that will be developed in schools, namely the Pancasila student profile and the Rahmatan Lil Alamin student profile (P5PPRA). The role of the madrasah principal as an education supervisor is needed to provide supervision, assistance, and support in improving the quality of the P5PPRA program. The research method used is qualitative, with inductive data analysis. This research uses a phenomenological approach, which is a type of qualitative research that looks at and listens to more detailed explanations and individual understandings of experiences. The supervision methods used included classroom observation, classroom visits, and open discussions with teachers. Academic supervision has an impact on the quality of human resources in madrasahs, ensuring that P5PPRA is more focused and improving student competence, because quality human resources and the ongoing educational process can be monitored continuously to ensure education services that are centered on student needs.